2015
DOI: 10.14393/bj-v31n4a2015-26173
|View full text |Cite
|
Sign up to set email alerts
|

Presence of antibodies against Leptospira spp. in dogs of Uberlandia, MG, Brazil

Abstract: ABSTRACT:The aim of this study was to investigate the occurrence of antibodies against Leptospira spp. and risk factors related to the epidemiology of leptospirosis in dogs living in the urban area of the municipality of Uberlandia, Minas Gerais, Brazil. Blood serum samples were examined from 268 dogs from the municipality's North, South, East, West and Central sanitary districts. The samples were collected during an animal vaccination campaign against rabies in August 2008. The occurrence of antibodies agains… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 10 publications
1
2
0
Order By: Relevance
“…The prevalence rate found in this study (13.2%) was similar to the 13.1% found by Magalhães et al (2007) in the city of Belo Horizonte, MG and lower than the 28.3% reported by Castro et al (2015) (FERNANDES et al, 2013).…”
Section: Contentssupporting
confidence: 73%
“…The prevalence rate found in this study (13.2%) was similar to the 13.1% found by Magalhães et al (2007) in the city of Belo Horizonte, MG and lower than the 28.3% reported by Castro et al (2015) (FERNANDES et al, 2013).…”
Section: Contentssupporting
confidence: 73%
“…The predominance of the serogroup Icterohaemorrhagiae is not a common finding when compared to studies carried out in recent years in other regions of Brazil. In the Southern region, the most common serogroups were Canicola and Autumnalis (Morikawa et al 2015, Oliveira et al 2016, Hafemann et al 2018, Pinto-Ferreira et al 2019, in Minas Gerais the serogroups Autumnalis, Tarassovi, Canicola and Grippotyphosa (Castro et al 2015), in Pará, Canicola, Semaranga and Icterohaemorrhagiae (Paz et al 2015), and in Piauí, the serogroups Canicola, Autumnalis and Australis were the most frequent (Silva et al 2017a).…”
Section: Discussionmentioning
confidence: 97%
“…Canine leptospirosis has been studied to some extent in Brazil (Castro et al, 2015, Sales et al, 2020, however these studies have been few and far apart. In 2002, the isolation of a Leptospira interrogans strain of the Canicola serovar, revealed that, of 105 canine tested the same year, 55 (52.4%) were reactive in the MAT (Brod et al, 2005).…”
Section: Introductionmentioning
confidence: 99%